Monepantel pharmaco-therapeutic evaluation in cattle: Pattern of efficacy against multidrug resistant nematodes - Cantón, Candela (2021)
The goal of the current work was to perform an integrated evaluation of monepantel (MNP) pharmacokinetics (PK) and pharmacodynamics, measured as anthelmintic efficacy, after its oral administration to calves naturally infected with GI nematodes resistant to ivermectin (IVM) and ricobendazole (RBZ) on three commercial farms. On each farm, forty-five calves were randomly allocated into three groups (n = 15): MNP oral administration (2.5 mg/kg); IVM subcutaneous (SC) administration (0.2 mg/kg); and RBZ SC administration (3.75 mg/kg). Eight animals from the MNP treated group (Farm 1) were selected to perform the PK study. Drug concentrations were measured by HPLC. The efficacy was determined by the faecal egg count reduction test (FECRT). MNP and MNP-sulphone (MNPSO2) were the main analytes recovered in plasma. MNPSO2 systemic exposure was markedly higher compared to that obtained for MNP. Higher Cmax and AUC values were obtained for the active MNPSO2 metabolite (96.8 ± 29.7 ng/mL and 9220 ± 1720 ng h/mL) compared to MNP (21.5 ± 4.62 ng/mL and 1709 ± 651 ng h/mL). The MNPSO2 AUC value was 6-fold higher compared to the parent drug. Efficacies of 99% (Farm 1), 96% (Farm 2) and 98% (Farm 3) demonstrated the high activity of MNP (P < 0.05) against GI nematodes resistant to IVM (reductions between 27 and 68%) and RBZ (overall efficacy of 75% on Farm 3). While IVM failed to control Haemonchus spp. and Cooperia spp., and RBZ failed to control Coooperia spp. and Ostertagia spp., MNP achieved 100% efficacy against Haemonchus spp., Cooperia spp. and Ostertagia spp. However, a low efficacy of MNP against Oesophagostomum spp. (efficacies ranging from 22 to 74%) was observed. In conclusion, oral treatment with MNP should be considered for dealing with IVM and benzimidazole resistant nematode parasites in cattle. The work described here reports for the first time an integrated assessment of MNP pharmaco-therapeutic features and highlights the need to be considered as a highly valuable tool to manage nematode resistant to other chemical families.